Mitigating Health Risks Through Biosorption: Effective Removal of Nickel (II) and Chromium (VI) from Water with Acid-Treated Potato Peels - Northaqifah Hasna Mohamed Khir; Nur Fatien Muhamad Salleh; Noraini Abdul Ghafar; Nurasmat Mohd Shukri (Jurnal Kesehatan Lingkungan)
Introduction: Nickel (Ni(II)) and chromium (Cr(VI)) are associated with serious health risks, including respiratory problems, kidney damage, and cancer, along with potential threats to ecosystems. Given their persistence and significant toxicity, effective removal from contaminated water is essential to mitigate these health risks. This study explores the efficacy of acid-treated potato peels (ATPP) as an economical and readily accessible biosorbent for the removal of Ni(II) and Cr(VI) from water solutions. Methods: The study explored two biosorbents: raw potato peels (RPP) and ATPP. Fourier Transform Infrared (FTIR) spectroscopy was utilized to analyze changes in surface functional groups. Batch biosorption experiments were performed using distinct contact times (30-180min), pH (3–11), and biosorbent dosages (0.1–0.5 g). The Mann-Whitney U test was applied for the statistical analysis. Results and Discussion: The FTIR analysis indicated an enhancement in carboxyl groups on the ATPP surface after acid treatment, with stronger transmittance peak at 1645 cm⁻¹. ATPP showed significant improvements in biosorption capacity compared to RPP, removing 18.23% of 10 mg/L Ni(II) at pH 5 in 120minutes using 0.5 g of ATPP. For Cr(VI), 52.28% removal was achieved at pH 7 with 0.2 g of ATPP within the same time frame. Statistical analysis confirmed the superior performance of ATPP in removing Ni(II) (p = 0.024) and Cr(VI) (p = 0.004). Conclusion: ATPP offers significantly higher biosorption capabilities than RPP attributed to the increased presence of carboxyl groups on the modified surface, indicating potential for eco-friendly effective material in mitigating the heavy metal pollution's health risks.